Yield Performance of Different Lentil Varieties under Different Sowing Dates - Mandi, Gaban; Sarkar, N. C.; Palai, Jnana Bharati (International Journal of Economic Plants, 2015)
The experiment was conducted at agricultural farm of Palli Siksha Bhavana, Visva-Bharati at Sriniketan of Birbhum district,West Bengal during rabi season of 2014-15 in red and lateritic soil to study the effects of different sowing dates on growth of different lentil varieties. The soil at experimental site was analysed sandy loam in texture with low in available N, medium in available P2O5 and K2O and slightly acidic (pH: 5.79) in nature. The experiment consisted of three levels of sowing dates (i.e. 31st October, 15th November and 30th November) and four levels of lentil varieties (i.e. L 4710, RKL 607-1, PL 406 and KLS 218) thus making twelve treatment combinations which were replicated thrice and was laid out in factorial randomized block design and grain yield, stalk yield and harvest index were recorded.